The SIRT6-Autophagy-Warburg Effect Axis in Papillary Thyroid Cancer - Zhou Yang; Renhong Huang; Xiyi Wei; Weiping Yu; Zhijun Min; Min Ye (Frontiers in Oncology, 2020)
As shown in our previous study, SIRT6 promotes an aggressive phenotype and the epithelial-mesenchymal transition (EMT) in papillary thyroid cancer (PTC). In this study, we focused on the regulatory axis including SIRT6, autophagy, and the Warburg effect. We innovatively confirmed that SIRT6 overexpression depleted histone H3 lysine 56 acetylation (H3K56ac) of the negative regulator of reactive oxygen species (NRROS) in vitro, thus increasing reactive oxygen species (ROS) production. The accumulated ROS then activated endoplasmic reticulum stress (ER stress) and subsequently induced autophagy. Furthermore, SIRT6 overexpression inhibited glucose transporter 1 (GLUT1) via autophagy-mediated degradation, ultimately suppressing the Warburg effect. Treatment with the ROS scavenger N-acetyl-L-cysteine (NAC, 5 mM) or the autophagy inhibitor chloroquine (CQ) both rescued the inhibition of the Warburg effect. Additionally, a higher concentration of NAC (15 mM) further inhibited the Warburg effect. These concentration-dependent bilateral effects of NAC on this process were confirmed to be due to the regulation of the AMPK signaling pathway. Finally, we further examined this mechanism in vivo by establishing subcutaneous xenografts in nude mice and analyzed the tumors using 18F radio-labeled fluorodeoxyglucose (18F-FDG) PET/CT. In conclusion, we identified a SIRT6-ROS-ER stress-autophagy-GLUT1-Warburg effect axis in PTC, which may provide a new therapeutic target. In addition, NAC (low concentration) and CQ, previously considered to be tumor inhibitors, were shown to promote tumorigenesis in PTC with high SIRT6 expression by inducing the Warburg effect.